Investigation of the carbohydrates of Camelina sativa (L.) Crantz and Camelina microcarpa Andrz - Tsykalo, T.; Trzhetsynskyi, S. D.; Тржецинський, Сергій Дмитрович (My University, 2021)
The aim of the workwas to study the monosaccharide composition of WSPS, PS and HC, isolated from the raw materi-als of Camelina sativa and Camelina microcarpa and to establish the quantitative content of these fractions.Materials and methods. The analysis of the composition of biologically active substances of carbohydrate nature was carried out in herb and seeds of Camelina sativa (variety “Slavutych”) and Camelina microcarpa. Samples of seeds for growing plants were provided by the National Center for Genetic Resources of Plants of Ukraine (The Plant Production Institute ND. V.YA. YURIEVA, NAAS of Ukraine).For the studies, the carbohydrates were separated by the Bailey method into monosaccharide fractions, which were used for TLC and quantification using a modified Dreywood spectrophotometric method with anthrone reagent in con-centrated sulfuric acid.Results.The presence of glucose, galactose and arabinose was determined in the hydrolysates of polysaccharide frac-tions of Camelina sativa of herb and seeds. Galactose, glucose, arabinose and xylose were found in the hydrolysates of polysaccharide fractions of Camelina microcarpa herb and seeds. The highest content of WSPS was determined in the herb of Camelina sativa, and the lowest -in the seeds of Camelina microcarpa. PS in the largest number were also found in the herb, and in the smallest –in the seeds of Camelina sativa. The content of the amount of HC was the high-est in the herb of Camelina sativa, and the smallest –in the seeds of Camelina sativa.Conclusions.The presence of 3 monosaccharides in the raw material of Camelina sativa and 4 monosaccharidesin the raw material of Camelina microcarpa was established by TLC. The quantitative content of monosaccharide fractions was determined by the spectrophotometric method, which in total predominated in Camelina sativa
Keywords: carbohydrates; WSPS; PS; HC; Camelina sativa (L.) Crantz; Camelina microcarpa Andrz.; TLC; spectro-photometric research